LEGAL OBLIGATION OF OUTSOURCING BUSINESS ACTIVITIES BASED ON CREATION OF EMPLOYMENT LAW - Saritua Silitonga; Muhammad Hasbi; Muhammad Dhobit Azhary Lubis; Avib Setian (Sean Institute, 2022)
In essence, every person or human (zoon politicon) always tries as much as possible to establish cooperative relationships in the field of law with other people. Before outsourcing was legalized in Indonesia,employment relationship problems are established based on the legal norms contained in the Civil Code or the Civil Code (Burgerlijk Wetboek) abbreviated as BW.The legal norms referred to are adapted to the noble values ​​contained in the five precepts of the Pancasila, and constitutionally they should not conflict with the 1945 Constitution. The problem raised in this thesis is the legal obligation of outsourcing business actors based on the omnibus law and what are the obstacles in its implementation. the role of outsourcing business actors, especially PT. Global Permai Eternal. legal protection from employment agencies in the city of Medan. The law that regulates the employment agreement for a certain time, which basically still has shortcomings, so it is often said to be inconsistent, because the law that is applied is too broad and not specific.